Use of information technologies in administrative evidence proceedings – selected issues (Discourse of Law and Administration, 2023)
The article deals with the basic issues related to the use of modern information and communicationsolutions in administrative evidence proceedings. The assessment of the functionality ofthe electronic document, referred to in Article 3(2) in conjunction with Article 3(1) of the Act onInformatisation of the Activities of Entities Performing Public Tasks in administrative evidence proceedings,in the context of changes in the Code of Administrative Procedure resulting from the Acton Electronic Delivery of Documents, was treated as particularly important. In connection with theresignation – as a result of the amendment – from using i.e., the following terms: “electronic document”,“form of an electronic document” within the meaning of the Act on Informatisation of theActivities of Entities Performing Public Tasks, the assessment of the legal character of an electronicdocument in administrative proceedings becomes an even more complex legal issue than it usedto be. It is therefore fundamental to define the semantic scope of the term “electronic document” inlegal terms in the context of regulations of the Code and to assess its essence and function in thephase of administrative evidence proceedings. In particular, it will be crucial to determine the relationshipbetween the “document recorded in electronic form” within the meaning of Article 14 § 1aof the Code of Administrative Procedure and the “electronic document”, as well as between it andthe document in electronic form admitted as evidence and other evidence recorded electronically inthe administrative evidence procedure.
Keywords: administrative proceedings; evidence proceedings; electronic document; electronically recorded letter; electronic material